A Comparative Study of the Structural Performance of Different Types of Reticulated Dome Subjected to Distributed Loads - Gythiel, Willem; Mommeyer, Christiaan; Raymaekers, Tom; Schevenels, Mattias (Frontiers in Built Environment, 2020)
Whereas reticulated domes (i.e. domes composed of bars) are very material-efficient in general, the geodesic dome is claimed to be superior according to its patent holder, Richard Buckminster Fuller. Recent studies on the optimal design of reticulated domes do not allow a direct comparison between the geodesic dome and other dome types because the test cases are not subjected to the same loads. This paper aims to determine which type of reticulated dome is superior in terms of material efficiency by comparing the minimized weight of different dome types, taking into account stress and buckling constraints. The study includes hemispherical Schwedler, Kiewitt and geodesic domes with a diameter of 16 m, and a gravity load of 2 kN/m². Full enumeration is used to optimize the discrete variables (number of rings, subdivisions along each ring,...), while a gradient-based algorithm is used for the continuous variables (member sections). The results show that the claim of uniform stressing in a geodesic dome is legitimate: if all members are assigned the same size, a geodesic dome is generally more evenly stressed and up to 28% lighter than other dome types of similar size. However, if all members are sized individually, the Schwedler dome is the lightest.